2022
DOI: 10.3390/ijerph191912278
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Public Participation in Community Disaster Mitigation Activities: A Comparison of Model and Nonmodel Disaster Mitigation Communities

Abstract: Public participation in community-organized disaster mitigation activities is important for improving disaster mitigation capacity. With data from 260 questionnaires, this study compared the current status of public participation in model disaster mitigation communities and nonmodel communities in a geological-disaster-prone area. Three community-organized disaster mitigation education activities were compared cross-sectionally. A binary logistic regression was used to analyze the effects of attitude, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…This approach has proven to be adaptable during disaster preparedness and reconstruction. In terms of DM activities most studies have concluded that factors such as risk perception, disaster experience (Peng et al, 2019), knowledge of participation mechanisms (Uchida et al, 2021), trust (Que et al, 2022), and demographic characteristics (Matias, 2020) will influence individuals and families to take DM measures. However, few empiric al studies have examined the impact of exogenous shocks, such as labor out‐migration, on the DM behavior of peasant households.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has proven to be adaptable during disaster preparedness and reconstruction. In terms of DM activities most studies have concluded that factors such as risk perception, disaster experience (Peng et al, 2019), knowledge of participation mechanisms (Uchida et al, 2021), trust (Que et al, 2022), and demographic characteristics (Matias, 2020) will influence individuals and families to take DM measures. However, few empiric al studies have examined the impact of exogenous shocks, such as labor out‐migration, on the DM behavior of peasant households.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the appropriateness of these perspectives has demonstrated to be effective in mitigating susceptibility and exposure to disasters. Nonetheless, numerous social researches assent that the threshold of cultural community exposure foresight is significantly associated to strength and exposure peril reduction (Nkombi and Wentink, 2022;Que et al, 2022;Johnston et al, 2022). Since these initiatives are developed at proletariat statuses, they are judged germane in generating appropriate responses to the peril of typhoon activated deluge in Western Rural and Urban, Sierra Leone.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, China initiated the establishment of the National Comprehensive Disaster-Reduction Demonstration Community (NCDDC). According to the established standard of the NCDDCs and the relevant literature, an NCDDC is defined as a community, both urban and rural, that integrates the promotion of emergency knowledge, the establishment of emergency facilities, and the enhancement of residents' self-rescue and mutual aid capabilities [14,17,18]. As the model for community disaster reduction, the NCDDC plays a leading, demonstrative, and radiating role in enhancing China's comprehensive disaster reduction capacity at the grassroots level.…”
Section: Introductionmentioning
confidence: 99%